Cultural considerations in health care capacity building: A qualitative study in Lesotho. Issue 9 (2nd September 2022) - Kulesa, John; Chua, Ian; Crawford, Lexi; Thahane, Lineo; Sanders, Jill; Ottolini, Mary; Ferrer, Kathy
ABSTRACT: International non-governmental organisations (NGOs) and academic institutions support health care capacity building to strengthen health systems in low and middle-income countries. We conducted a phenomenological study of foreign and Basotho clinicians who participated in clinical continuing professional development (CPD) in Lesotho. Clinicians included physicians, nurses, and a nutritionist. We sought to understand, through the lens of social cognitive theory, how cultural differences between foreign and Basotho clinicians affected bidirectional clinical education led by NGOs and academic institutions. We also assessed how Basotho clinical educators considered culture when leading NGO-sponsored clinical CPD for Basotho clinicians. After analysing 17 interviews with 24 total participants (four foreign educators, 11 Basotho educators, and nine Basotho learners), using an iterative and inductive approach, we identified 17 themes within the cognitive, environmental, and behavioural domains. Key findings highlighted: (1) cultural tensions between foreign and Basotho culture, including bias against traditional culture; (2) power structures which affected the efficacy of in-service training strategies; (3) perceptions among foreign educators that technical assistance was more effective than direct service delivery at promoting education and sustainability. Educators should map out key relationships and engage local and foreign stakeholders in culturally-focused targeted needs assessments to improve curricular design in capacity building.